Pelatihan Mendesain Soal Literasi Matematika Menggunakan Budaya Bangka Belitung - Putra, Yudi; Vebrian, Rajab (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
Mathematical literacy ability is an ability that must develop from an early age. How one can use mathematical abilities in daily life is the goal of digital education. Nowadays, the role of mathematics has replaced by technology; mathematical calculations nowadays have many sophisticated tools with fast counts. A trader no longer needs to memorize multiplications to calculate profit and loss; there is already a faster calculator. Also, complex calculations can use computers to complete. Methods in activities Training in designing mathematical literacy questions using the Bangka Belitung context for elementary school teachers, namely 1) Preparation: a) Literature Study on PISA Mathematics Assessment of Indonesian students; b) Literature Study concerning mathematical literacy questions; c) Literature Study of mathematical literacy journals in PISA; d) Design training concepts. 2) Implementation: a. Providing an understanding of the mathematical problems of the PISA model, Mathematical Literacy, scientific questions using context; b) Providing an understanding of the math problems of the TIMSS model, Mathematical Literacy, scientific questions using context; c) Training in making scientific literacy questions using the Bangka Belitung context. The training to design mathematics literacy questions using the context of the Bangka Belitung for Elementary School Teachers in Simpang Katis Subdistrict hold at SD Negeri 5 Simpang Katis which was held on 18 to 21 July 2018. The implementation of this activity was based onsupport from the STKIP Muhammadiyah Bangka Belitung campus through LPPM and supported by the Principal of SD Negeri Simpang Katis, Mr Mulkan, S.Pd., SD, along with the board of teachers and staff Kemampuan literasi matematika merupakan kemampuan yang harus ditumbuhkembangkan dari sejak dini. Bagaimana seseorang dapat menggunakan kemampuan matematika dalam kehidupan sehari - hari itu merupakan tujuan dari pendidikan diera digital. Saat ini peran matematika sudah banyak digantikan oleh teknologi, perhitungan matematika saat ini sudah banyak alat yang canggih dengan hitungan cepat. Seorang pedagang sudah tidak perlu lagi hafal perkalian untuk menghitung laba dan rugi, sudah ada kalkulator yang lebih cepat. Selain itu juga, perhitungan yang rumit dapat menggunakan komputer dalam menyelesaikan. Metode dalam kegiatan Pelatihan mendesain soal literasi matematika menggunakan konteks Bangka Belitung untuk Guru SD, yakni 1) Persiapan: a) Studi Pustaka tentang Penilaian Matematika PISA siswa Indonesia; b) Studi Pustaka mengenai soal-soal literasi matematika; c) Studi Pustaka jurnal literasi matematika dalam PISA; d) Desain konsep pelatihan. 2) Pelaksanaan: a. Memberikan pemahaman mengenai soal matematika model PISA, Literasi Matematika, soal-soal matematika menggunakan konteks; b) Memberikan pemahaman mengenai soal matematika model TIMSS, Literasi Matematika, soal-soal matematika menggunakan konteks; c) Pelatihan dalam membuat soal-soal literasi matematika menggunakan konteks Bangka Belitung. Kegiatan pelaksanaan pelatihan mendesain soal literasi matematika menggunakan konteks Bangka Belitung untuk Guru SD se-Kecamatan Simpang Katis ini dilaksanakan di SD Negeri 5 Simpang Katis yang dilaksanakan pada tanggal 18 sampai dengan 21 Juli 2018. Terselenggaranya kegiatan ini berdasarkan dukungan dari kampus STKIP Muhammadiyah Bangka Belitung melalui LPPM, dan didukung oleh Kepala Sekolah SD Negeri Simpang Katis Bapak Mulkan, S.Pd., S.D., beserta dewan guru dan staf.